Thermodynamic control of MEMS meteorology pressure sensing element in low‐temperature application down to −45°C. Issue 7 (1st October 2017) - Du, Lidong; Zhao, Zhan; Fang, Zhen; Feng, Yu; Yan, Jize
Abstract : In this study, the authors present an alternative method for poor accuracy of piezoresistive meteorology pressure sensing in low‐temperature environment (down to −45°C) by incorporating external thermodynamic control. In order to use the designed sensor in such a low‐temperature environment, the microelectromechanical systems (MEMS) chip itself has to be kept at 50°C, which is the most common used highest working temperature in meteorology field. The heat compensation is achieved by a pulse‐width modulation controlled heating resistor based on proportional–integral–derivative algorithm. The precision of thermal control was obtained at 50 ± 0.5°C during the bench test. The simulation results from COMSOL software are consisted with lumped element model analysis. Under the condition of environmental temperature down to −45°C, system achieved a maximum absolute error within ±0.5 hPa after pressure calibration.